2009
DOI: 10.1111/j.1442-2042.2009.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Radical retropubic prostatectomy with running vesicourethral anastomosis and early catheter removal: Our experience

Abstract: Objectives: To assess the outcomes of patients undergoing radical retropubic prostatectomy (RRP) with a running vesicourethral anastomosis and catheter removal on postoperative day 3 or 5. Methods: From February 2006 through December 2007, 55 patients underwent RRP at our institution. All procedures were performed by a single surgeon using a running suture for the vesicourethral anastomosis. A cystogram was carried out before catheter removal in all patients. The initial 23 of 55 patients (Group 1; n = 23) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…In addition, we found that the incidence of anastomotic strictures was significantly higher in patients with an anastomosis constructed by the interrupted suture technique than in those with the running suture technique. This finding is consistent with those reported by Ozu et al .,6 who found that the use of running sutures in these patients is safer compared with the use of four to six interrupted sutures, allowing safe early catheter removal in most patients. We speculate that the running suture technique decreases prolonged anastomotic urinary leakage and bleeding, which may lead to local ischemia or blood clot accumulation, delay mucosa healing and result in urinary extravasation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found that the incidence of anastomotic strictures was significantly higher in patients with an anastomosis constructed by the interrupted suture technique than in those with the running suture technique. This finding is consistent with those reported by Ozu et al .,6 who found that the use of running sutures in these patients is safer compared with the use of four to six interrupted sutures, allowing safe early catheter removal in most patients. We speculate that the running suture technique decreases prolonged anastomotic urinary leakage and bleeding, which may lead to local ischemia or blood clot accumulation, delay mucosa healing and result in urinary extravasation.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, various procedures exist for managing anastomotic strictures25678 after radical prostatectomy, including single sounds or balloon dilation, cold knife incision, transurethral resection or internal urethrotomy with a Holmium laser. However, none of these methods is universally accepted due to the relatively high recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…2). 9 After eversion of the bladder mucosa with bladder neck preservation, an anchoring suture was placed at the 6 o'clock position 5 mm posterior to the bladder neck using 3-0 poliglecaprone (3-0 Monocryl, SH, 90 cm, double-armed needle). A one-sided needle was driven from outside-in to the bladder mucosa at the 5 o'clock position; it passed the 5 o'clock position of the urethral stump with an inside-out full-thickness suture.…”
Section: Surgical Technique and Postoperative Examinationsmentioning
confidence: 99%
“…The middle of the running suture was secured with several LAPRA-TY ® clips (Ethicon Inc., Bridgewater, NJ, USA). We attempted to push the needles thinly through the anterior urethra (15) and anchor them to the fascia covering the DVC to avoid laceration of the urethra. The double-armed running sutures were finally ligated at the anterior side of the urethra.…”
Section: Methodsmentioning
confidence: 99%